Impedance Characterization and Modeling of Gold, Silver, and PEDOT:PSS Ultra-Thin Tattoo Electrodes for Wearable Bioelectronics - Mascia, Antonello; Collu, Riccardo; Makni, Nasreddine; Concas, Mattia; Barbaro, Massimo; Cosseddu, Piero (Sensors (Basel, Switzerland), 2025)
This study presents a comprehensive evaluation and an equivalent circuit modeling of the skin–electrode impedance characteristics of three types of ultra-thin tattoo electrodes, all based on Parylene C nanofilms but with different active materials: Gold, Silver, and PEDOT:PSS. Their performance was compared to standard disposable Ag/AgCl electrodes. Impedance measurements were carried out on six human subjects under controlled conditions, assessing the frequency response in the range of 20 Hz to 1 kHz. For each subject, the impedance was recorded six times over one hour to investigate the stability and the temporal performance. The collected data were subsequently analyzed to model the electrical properties and interface behavior of each electrode type. The findings demonstrate that the tattoo electrodes offer impedance levels comparable to those of Ag/AgCl electrodes (in the order of tens of kΩ at 20 Hz), while providing additional benefits such as enhanced conformability, improved skin adhesion, and reduced skin irritation during use. Furthermore, the modeling of the skin–electrode interface through a more detailed equivalent circuit than the single time constant model enables a more detailed interface analysis and description, with fitting algorithm R2 scores of about 0.999 and 0.979 for the impedance magnitude and impedance phase, respectively. The proposed equivalent circuit offers valuable insights for optimizing electrode design, supporting the potential of Parylene C-based tattoo electrodes as promising alternatives for next-generation wearable bioelectronic applications.